Formen arthurischen Erzählens vom Mittelalter bis in die Gegenwart - Dietl, Cora; Schanze, Christoph; Paris, Erik; Ravasio, Paola (Schriften der Internationalen Artusgesellschaft, 2016)
"The essays assembled in this volume illuminate various facets of Arthurian narrative. They compare narrative aspects of French and German Arthurian literature from the medieval period, address questions surrounding the réécriture ("rewriting") of Arthurian legend in the Late Middle Ages, and explore how the Arthurian tradition has "lived on" in other narrative formats, including musical theater, film, and the contemporary novel."--
Band erscheint [aus] Anlass [des] 75. Geburtstag[es] Friedrich Wolfzettels, des Gründers dieser Reihe
Keywords: Aufsatzsammlung; Festschrift; Geschichte; Artusepik